“Assim na terra como no céu” : o conflito entre o Estado e a Igreja Católica em Roraima (1968-1988) - Oliveira, Whitney França de (2018)
Between 1962 and 1965 the Catholic Church held the Second Vatican Council, one of the great reforms of Catholicism. In Latin America the Theology of Liberation arise, which permeated the missionary activity of the Church’s progressive wing. With emphasis on Human Rights and Social Justice, left-wingers are making a preferential option for the poorest and the most oppressed. In the Federal Territory of Roraima, the Consolata Catholic Order opted for Indian’s causes and abandoned the catechesis of the relief. The new activity of the Church has generated conflicts with the Military State. The Military Government started in 1964, based on the National Security Doctrine, imposed a repressive policy in Brazil. In order to meet the national development goal, the militarys put into practice the Amazonian Integration policy to the rest of the country, centered on National Security. However, the military ideology did not take into account the way of life of the Indians, causing the death of several people. The research investigates the attitude of the government against the activism of the consolatinos between 1968 and 1988.